Enhancing Critical Thinking through Questioning: A Case of Teaching Short Stories - Dahal, Dadhiram (Koshi Pravah: Multidisciplinary Peer Reviewed Journal, 2022)
Using questioning techniques in teaching short stories is a tool to enhance understanding and higher order thinking. Questioning is believed to allow students to participate in the teaching learning process and helps to develop critical thinking skills. It is a reflective model that helps students to evaluate a shared experience or an event so that they can identify ways to improve or act. But many English teachers in Nepal do not teach the students how to ask the right questions. Instead, they provide answers only. Also, the classes teaching English as Foreign Language in our context are not equipped with adequate resources for teaching and learning activities. Such low - resourced classes can be made engaging and effective through questioning. On this background, this paper explores the role of questioning in teaching short stories and attempts to implement the questioning technique in a short story included in the English textbook of Grade 12 in Nepal. To implement the questioning technique, Bloom's taxonomy is used as a tool to propose the teaching of the short story “A Devoted Son” written by Anita Desai. This study is based on the empirical evidence of using questioning techniques in the real classes for a week in Koshi St. James School, Itahari, Sunsari. The study was conducted among 60 students of two different sections using diagnostic tests, observation and discussion tools. Result of this study reveals that the students in English classes are more engaged and activated through the questioning technique implemented while teaching short stories and other texts in contrast with the students who are taught without the questioning.